PENGARUH KEPUASAN TERHADAP LOYALITAS DENGAN KEPERCAYAAN MEREK SEBAGAI VARIABEL MEDIASI (STUDI EMPIRIS PENGGUNA BLACKBERRY DI UNIKA WIDYA MANDALA MADIUN) - Kurniawati, Dyah (Widya Warta, 2016)
The aim of this research was to analyze the impact of satisfaction on loyalty to the brand trust as a mediating variable. The population in this study is the Blackberry users in Unika Widya Mandala Madiun, using purposive sampling. The analysis technique using path analysis. The result of this research shows thatÂ  satisfaction variables directly influence the trust and loyalty. Variable trust direct effect on loyalty. Variable satisfaction indirect effect on loyalty through brand trust.